Aree Lkhua Song: A Musicological Analysis of Pakapel Tradition Among the Kelabit Tribe in the Upper Baram River, Sarawak. - Abdullah, Mohd Hassan; Ramli, Nor Azman Mohd; Nasrifan, Mohd Nizam; Rahim, Mahayuddin Abdul; Sulong, Mohd Azam (International Journal of Psychosocial Rehabilitation, 2020)
The Kelabit are among the indigenous tribe dwelling in about sixteen small villages deep in the Borneo tropical rainforest near to the Indonesian border. The nearest town is Miri, which is only accessible via logging dirt road or a nineteen-sitter airplane served by Mas Wings rural air service. The tribe who mostly settled in longhouses used to be known with their headhunting tradition possess a very unique musical culture. Aree lakhua is a match-making song sung by young unmarried women in Pakapel tradition to attract single man to marry her. With the intrusion of western musical culture as well as the influence of Christianity in the society, this tradition is now no longer widely practiced and soon will be extinct. This work aims to reveal and analyse the musical aspect of the pakapel tradition among the Kelabit society. Using a combination of musicological and ethnographic approaches, the author presents the functional facts as well as analysing the musical aspects of the song. This work, complete with audio and video materials as well as musical transcription, contributes not only to ethnomusicological theory and method but also to a deeper understanding of the Kelabit musical culture.